128 Improving learning from incidents – taking a local approach through DRM. (22nd November 2019) - Zeitlin, Deborah; Banaghan, Maria; Price, Jessica; Scott, Emma
Abstract : Background: Concerns have long been raised of a chronic backlog of incident reports (Datix) pending investigation by managers, with 362 outstanding at the beginning of 2019. This was compounded by poor completion of the 'actions taken' field, and vitally, dissemination of learning points from the incident. Little guidance or training exists, and there are no formal pathways of learning dissemination from these investigated incidents, either through the immediate team or to the wider hospital staff. Aim: This Quality Improvement and Culture Change project aims to optimise the incident investigation process by: dispelling any culture of blame that may still be perceived; improve investigative competence and whole team learning; provide transparency to the whole team; establish shared learning of the outcomes; build a robust vehicle for the dissemination of this learning across the Trust and beyond. Method: Introduction of area based, weekly, 15 minute forums (Datix Review Meetings: DRMs) to facilitate the completion of topic appropriate incidents by the multidisciplinary team. Written guidance for decision making and completion of the incident report developed and disseminated to DRM facilitators along with specific training. Development and delivery of a weekly Educational email-shot with 3 most salient learning points distilled from the weeks DRM's across all areas within the division. Results: The initiative was only commenced July 2019, but anecdotal evidence is positive at this time. A pre-intervention questionnaire was completed in June 2019, to assess the safety culture prior to the intervention, with two further surveys to be completed as outcome measures of the intervention in January 2020 &amp June 2020.